2004
DOI: 10.1177/107110070402500507
|View full text |Cite
|
Sign up to set email alerts
|

Fibular Position in Relation to Lateral Ankle Instability

Abstract: This study supports the hypothesis that a posteriorly positioned fibula predisposes to ankle instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
2
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 10 publications
3
53
2
3
Order By: Relevance
“…They also used the axial malleolar index. 1 The differences in the aforementioned studies and the studies that have reported an anterior fibular position are in the measurement technique. Mavi et al 19 and our current study examined the position of the fibula in direct relation to the tibia in the sagittal plane.…”
Section: Cai Groupmentioning
confidence: 78%
See 2 more Smart Citations
“…They also used the axial malleolar index. 1 The differences in the aforementioned studies and the studies that have reported an anterior fibular position are in the measurement technique. Mavi et al 19 and our current study examined the position of the fibula in direct relation to the tibia in the sagittal plane.…”
Section: Cai Groupmentioning
confidence: 78%
“…19 Despite this evidence of anteriorly positioned fibula, 3 recent studies reported the fibula to be posteriorly positioned in those with acute ankle sprains. 1,7,24 Eren et al 7 prospectively examined the position of the fibula after acute inversion ankle sprain compared with a control group of uninjured ankles. A CAT scan compared the axial malleolar index.…”
Section: Cai Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no generally accepted opinion about positional faults of the fibula after LAS [4][5][6][7][8][9] . Our data suggest that subjects with greater differences in fibular position have more swelling as measured by differences in ankle girth.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined fibular position in subjects with ankle instability [4][5][6][7][8] . However, the results of these studies are inconclusive.…”
Section: Introductionmentioning
confidence: 99%